La educación - Escudero, Ethel (Revista Chilena de Humanidades, 2015)
The author outlines a set uf complex matters that have a bearing on the theory and practice of educational task, after which she presents sorne critica! reflexions on the aims of education, in relatiun with humanism in the widest sense of the term. She alludes to the most important positions of the present concerning the process of education, expressing, together with the German thinker Jaeger, that it is one that should lead man to the attainment of the "true goal of his life", a statement that leads to the formulation of difflerent criteria conceming the objectives of education , and which is dealt with as a science in the last part of this paper.